A novel inhibitor of activated thrombin-activatable fibrinolysis inhibitor (TAFIa) – Part I: Pharmacological characterization - Wang, Yi-Xin; Zhao, Lei; Nagashima, Mariko; Vincelette, Jon; Sukovich, Drew; Li, Weiwei; Subramanyam, Babu; Yuan, Shendong; Emayan, Kumar; Islam, Imadul; Hrvatin, Paul; Bryant, Judi; Light, David R.; Vergona, Ronald; Morser, John; Buckman, Brad O. (Thrombosis and Haemostasis, 2007)
We have discovered a novel small-molecule (3-phosphinoylpropionic acid) inhibitor of activated thrombin activatable fibrinolysis inhibitor (TAFIa), BX 528, which had an IC50 of 2 nM in an enzymatic assay and 50 nM in an in-vitro clot lysis assay, with 3,500- to 35,000-fold selectivity against other carboxypeptidases, such as CPN, CPZ and CPD, and 5- and 12-fold selectivity against CPE (CPH) and CPB, respectively. At 10 µM, BX 528 had no significant activity (< 50% inhibition or antagonism) in a panel of 137 enzymes and receptors. It had no effects on blood coagulation and platelet aggregation up to 300 and 10 µM, respectively. The plasma half-life following intravenous administration was 0.85 hours in rats and 4.5 hours in dogs. No significant metabolism was detected in human, dog or rabbit hepatic microsomes, and no significant inhibition of cytochrome P450 3A4 and 2D6 up to 30 µM. No cytotoxic or cell proliferative effects were found in three hepatic and renal cell lines up to 300 µM and no mutagenic activity was seen in the Ames II screen. There were no significant hemodynamic effects in rats and dogs up to 100 and 30 mg/kg with peak plasma drug concentrations of ~1,000 and 300 µM, respectively. In an in-vivo complement activation model in guinea pigs, BX 528 showed minimal inhibition of plasma CPN activity up to 60 mg/kg with peak plasma concentrations up to 250 µM. Thus, these data demonstrate that BX 528 is a novel, potent, selective and safe TAFIa inhibitor.
Keywords: TAFI; carboxypeptidases; potency; selectivity; safety; pharmacokinetics